(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Morphology of each larval instar of Phyllonorycter cerasicolellus (Herrich-Schaffer) is described. The species is hypermetabolic; the larvae I, II and III are sap-feeders, while IV and V tissue-feeders. Larvae II and III do not show regular-shaped spiracles of II-VII abdominal segment, but rudimentary structures. The antennae of sap-feeding larvae bear multiporous sensilla, similar to olfactory ones. Ph. cerasicolellus was collected from peach, plum and cherry in different sites in Northern Italy. The density of the populations tended to increase during last years. Notes are also given on life cycle and natural enemies.